Autism Spectrum Disorders and Schizophrenia Spectrum Disorders: Excitation/Inhibition Imbalance and Developmental Trajectories - Canitano, Roberto; Pallagrosi, Mauro (Frontiers in Psychiatry, 2017)
Autism Spectrum Disorders (ASD) and Schizophrenia Spectrum Disorders (SSD) share clinical and genetic components that have long been recognized. The two disorders co-occur more frequently than would be predicted by their respective prevalence, suggesting that a complex, multifactor association is involved. However, DSM-5 maintains the distinction between ASD, with core social and communication impairments, and SSD, including schizophrenia (SCZ), with hallucinations, delusions and thought disorder as essential features. ASD and SSD have common biological underpinnings that may emerge early in development and unfold over time. One of the hypotheses supporting the similarities in the social and cognitive disturbances of ASD and SSD relates to abnormalities in the ratio of excitatory to inhibitory cortical activity (E/I imbalance). E/I imbalance in neurodevelopmental disorders could be the consequence of abnormalities in genes coding for glutamatergic and GABAergic receptors or synaptic proteins followed by system derangements. Altered genes coding for synaptic proteins have been reported in both ASD and SSD and preclinical models have confirmed their role in synaptic transmission and relevant behaviors. SSD and ASD have been characterized as polygenic disorders in which to the onset and progression of disease is triggered by interactions among multiple genes. Mammalian Target of Rapamycin (mTOR) signaling is under intense investigation as a convergent altered pathway in the two spectrum disorders. Current understanding of shared and divergent patterns between ASD and SSD from molecular to clinical aspects is still incomplete and may be implemented by the Research Domain Criteria (RDoC) approach.